An Empirical Study On The Contribution Of Lean Practices To Sustainable Manufacturing: The Role Of Lean Culture As Moderator - Nezhad, Mahzad Bandeh (2011)

(untitled)
Nowadays, sustainabiIity issues receives an increasing level of attention at both global and local levels which eventually leads to questions on how to integrate sustainability with business operations and strategy. Despite the importance of lean manufacturing in alleviating sustainable manufacturing issues and providing environmental, economic and social benefits to organizations, little is known about the effect of lean practices on triple bottom line of sustainability. The purpose of this study is to investigate the effect of lean practices in different functional areas of manufacturing finns on sustainable manufacturing performance. Saat ini, masalah kelestarian menerima tahap peningkatan perhatian tinggi di peringkat global dan tempatan yang akhimya mengarah pada pertanyaan tentang bagaimana untuk mengintegrasikan kelestarian dengan operasi pemiagaan dan strategi. Walaupun pentingnya, pengeluaran Lean dalam mengurangkan masalah pengeluaran berterusan dan memberikan manfaat persekitaran, ekonomi dan sosial kepada organisasi, sedikit yang diketahui tentang pengaruh amalan ini terhadap kelesterian triple bottom line. Tujuan penyelidikan ini adalah untuk mengetahui pengaruh amalan Lean di bidang fungsi yang berbeza terhadap prestasi syarikat perkilangan pengeluaran kelesterian.